Association Between Nurses’ Knowledge and Practice Regarding Chemotherapy Induced Peripheral Neuropathy and Its Development in Cancer Patients: Chemotherapy Induced Peripheral Neuropathy - Ahmed Sohail , Muhammad; Afzal, Muhammad; Yaqoob, Adnan (Pakistan Journal of Health Sciences, 2022)
The adverse effects of peripheral neuropathy caused by chemotherapy include numbness, tingling, irritation, burning, difficulty keeping balance, and a chilling sensation. CIPN is one of the symptoms that has the potential to negatively impact the patient's quality of life (QoL), the treatment plan, and their overall safety. Objectives: To determine oncology nurses’ knowledge and practice regarding chemotherapy-induced peripheral neuropathy (CIPN) and its development in cancer patient. Methods: In a descriptive cross-sectional study, 172 registered nurses from two public hospitals were chosen with convenient sampling to see if there was an association between their knowledge and practice about chemotherapy-induced peripheral neuropathy in regard with its development in cancer patients. Three revised questioners were used to get information about nurses’ knowledge, practice and 1 questioner from patient about neuropathy development. (Knowledge, practice and neuropathy devolvement). Results: Knowledge showed that 56.4 % of participants had fair knowledge and Practice showed that 49.4 % of participants had fair practice, while 47.1% of patient had developed mild neuropathy. Chi square test was performed to see the association which showed a significant association between neuropathy development with nurses’ knowledge and practice as results were 0.000 (p-value is <0.005 taken as significant). Conclusions: There is a critical need to enhance oncology nurses' abilities in neurological assessment, and a reliable method of CIPN evaluation is essential. Guidelines for the treatment and evaluation of CIPN, as well as further studies in different health institutions to generalize the results across Pakistan, are urgently needed.